Challenging Islamophobia with Humor - The Example of the Datteltäter on Youtube - Kızılkaya, Zeynep Zelal (My University, 2023)
A new generation of Muslim youth in the West is using humor to cope with rising Islamophobia, racist immigration rhetoric and sexism. A representative of this new generation is the YouTube channel called Datteltäter. Drawing on social theories of humor and dissent, this study analyzes the content produced by Datteltäter, revealing that their humor is a practice of dissent and that they seek to subvert the dominant discourse through humour. Since humor is not a practice of opposition per se, its character at this point depends on its context, the distribution of sensibilities and its relationship to policing regimes, and the techniques it uses. In this study, where the online ethnography method was used, representative videos of the Datteltäter, selected with purposeful sampling, were described and analyzed. The study concluded that the Islamophobic and racist discourses and practices that daily life in German society and disperse the sensible in order to control bodies, and their seemingly meaningful hierarchy of emotions and ideas, are exposed through humor. The study also found that the new generation of Muslims have in-between insights that come from being together and have developed a similar oppositional attitude towards their communities. In doing so, they create a space of shared experiences and hybrid subjectivities that are open to others.
Keywords: YouTube; Islamophobia; Humor; New Generation Immigrants; Datteltäter